The Student Movement in Chile Origins, trajectory and impact - Beranová, Marie (2014)
Latin America cannot be conceived without acknowledging the social movements, which are often the engines of political and social changes on the continent. Until recently, Chile appeared to be the country where the social order was perceived as the most accomplished in relation to its politically unstable neighbouring countries, as well as in relation to its proper history. The 2011 student movement, which is the most significant social movement within the last twenty years of the Chilean history, can be completely understood only from a broader perspective of the 20th century. In order to understand the recent changes, the thesis deals with the phenomenon of the Chilean student movement studying its origins, historical trajectory and impact. The aim of the thesis is to explore the continuities and changes of the student movement and question why the 2011 protests are treated as a separate collective action in relation to the cycles of contention experienced in the 20th century.